Pengaruh Faktor Intrinsik, Faktor Ekstrinsik dan Sikap Konsumen terhadap Minat Menjadi Mitra Laku Pandai (Studi Pada Masyarakat Kota Pekalongan, Semarang, dan Yogyakarta) - Muchammad Kukuh Septialana; Aprillia Elly Kusumastuti (EBBANK, 2017)
The development of the banking industry is not accompanied by equitable access to services to the community as a whole. Community access to banking services is still low, especially for people living far from urban areas. The emergence of Laku Pandai considered able to overcome these problems. Laku Pandai serves financial transactions for people in rural areas. But in reality, the realization of the achievement of agent or Laku Pandai is still far from being targeted. This study aims to analyze the influence of intrinsic factor variables, extrinsic factor variables and consumer attitudes on the interest of being agents with research objects of the people of Pekalongan City, Semarang, and Yogyakarya. The results of multiple regression analysis of perceived quality, perceived value, perceived price, familiarization and perceived economic situation significantly influence the interest of being an agent. While the perceived risk, store image, advertising and trust does not affect the interest of becoming an agent.